Preventing the Progression of Knee Osteoarthritis: A Qualitative Study of Older Adults’ Experiences in Pekanbaru, Indonesia - Arneliwati Arneliwati; Masrul Masrul; Mudjiran Mudjiran; Meri Neherta (Universitas Pahlawan Tuanku Tambusai, 2026)
Osteoarthritis of the knee is a major health problem among older adults that can lead to disability and decreased quality of life. Preventing the progression of this disease requires a deep understanding of the experiences of older adults in managing their condition. This study aimed to explore the experiences of elderly individuals in preventing the progression of knee osteoarthritis in Pekanbaru City. This study used a qualitative design with a descriptive phenomenological approach. The participants consisted of 15 older individuals aged 60-80 years diagnosed with knee osteoarthritis, selected through purposive sampling. Data collection was conducted through in-depth semi-structured interviews from March to May 2024. The findings identified four main themes: (1) older adults’ understanding of knee osteoarthritis and its prevention, (2) strategies for managing pain and limited mobility, (3) family and social support in the prevention process, and (4) challenges and barriers in implementing prevention efforts. The results showed that the elderly have only a limited understanding of preventing the progression of osteoarthritis but display high motivation to take preventive measures when they receive adequate support. The most commonly used strategies included activity modification, traditional medicine and light exercise. Comprehensive ed Background: Knee osteoarthritis is a common chronic condition among older adults and is associated with disability and reduced quality of life. Efforts to prevent disease progression are strongly influenced by older adults’ experiences and perceptions in managing their condition. Aim: This study aimed to explore the experiences of older adults in preventing the progression of knee osteoarthritis in Pekanbaru, Indonesia. Methods: A qualitative study with a descriptive phenomenological approach was conducted among 15 older adults aged 60–80 years diagnosed with knee osteoarthritis. Data were collected through semi-structured in-depth interviews in Pekanbaru City from March to May 2024 and analyzed using thematic analysis following Braun and Clarke’s framework. Results: Four main themes were identified: (1) limited understanding of knee osteoarthritis and its prevention, (2) pain management strategies and adaptation of daily activities, (3) the role of family and social support in prevention efforts, and (4) physical, financial, and environmental challenges in implementing preventive behaviors. Despite limited knowledge, participants demonstrated strong motivation to prevent disease progression when adequate support was available. Conclusion: Older adults’ experiences indicate that prevention of knee osteoarthritis progression is shaped by knowledge, adaptive capacity, and social support. These findings highlight the need for structured education and a multidisciplinary, context-sensitive approach to support preventive efforts among older adults. ucational programs and multidisciplinary support are needed to improve the effectiveness of efforts to prevent the progression of knee osteoarthritis in older adults.